2011
DOI: 10.3945/ajcn.110.007393
|View full text |Cite
|
Sign up to set email alerts
|

Oral acetyl-l-carnitine therapy reduces fatigue in overt hepatic encephalopathy: a randomized, double-blind, placebo-controlled study

Abstract: Patients with HE treated with ALC showed a decrease in the severity of both mental and physical fatigue and an increase in physical activity. This trial was registered at clinicaltrials.gov as NCT01223742.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 63 publications
1
55
0
Order By: Relevance
“…The present data showed that L-carnitine reinforced the mitochondrial β-oxidation and the activity of the key ROS-scavenging antioxidant enzymes such as Sod2 and CAT without an increase in oxidative stress. In addition, L-carnitine has recently been shown to exhibit ammonia reduction in hepatic encephalopathy patients and improvement of fatigue, which reflects the wide pharmacological effects of L-carnitine on hepatic and muscular mitochondrial function recovery [24]. We were not able to demonstrate such effects of L-carnitine in our model, as we did not examine plasma ammonia levels or physical scores that reflect hepatic encephalopathy and related effects.…”
Section: Discussionmentioning
confidence: 90%
“…The present data showed that L-carnitine reinforced the mitochondrial β-oxidation and the activity of the key ROS-scavenging antioxidant enzymes such as Sod2 and CAT without an increase in oxidative stress. In addition, L-carnitine has recently been shown to exhibit ammonia reduction in hepatic encephalopathy patients and improvement of fatigue, which reflects the wide pharmacological effects of L-carnitine on hepatic and muscular mitochondrial function recovery [24]. We were not able to demonstrate such effects of L-carnitine in our model, as we did not examine plasma ammonia levels or physical scores that reflect hepatic encephalopathy and related effects.…”
Section: Discussionmentioning
confidence: 90%
“…Several reports have already cited the NH3-lowering effects of carnitine in cirrhosis (8,15,16), and levocarnitine is being adopted as a new therapeutic option for cases of cirrhosis accompanied by refractory hepatic encephalopathy that prove resistant to synthetic disaccharides and rifaximin. Carnitine is also used to treat hyperammonemia when using valproic acid and antimicrobials containing a pivoxil group (17).…”
Section: Discussionmentioning
confidence: 99%
“…Calibration was obtained using hydrogen peroxide (0.2–20 mmol/L). [32,33] The limit of detection for this assay is approximately 0.25 nmol/L.…”
Section: Methodsmentioning
confidence: 99%